The Influence of Good Corporate Governance Mechanisms and Profit Management (Empirical Study on Agricultural Sector Companies Listed on the Indonesia Stock Exchange in 2015-2018) - Siswanti, Febi; Hizazi, Achmad; Wijaya, Rico (Jurnal Cakrawala Akuntansi, 2023)
This study is entitled "The Effect of Good Corporate Governance Mechanisms and Earnings Management on Company Performance (Empirical Study of Agricultural Sector Companies Listed on the Indonesia Stock Exchange for the 2015-2018 Period)". The purpose of this study is to determine the effect of Good Corporate Governance Mechanisms and Earnings Management on Company Performance both simultaneously and partially. This study uses agricultural sector companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2018 period. The sampling technique used is purposive sampling. The sample used in this study was 14 companies. The data analysis technique used in this study is multiple linear regression analysis. The results of the hypothesis testing are as follows. (1) The mechanism of governance (Good Corporate Governance) in this case the proportion of the board of commissioners, the number of audit committees, institutional ownership and profit management has an effect on company performance, (2) The proportion of the board of commissioners has no effect on company performance, (3) The number of audit committees has no effect on company performance, (4) Institutional ownership has an effect on company performance, and (5) Profit management has an effect on company performance by20.5%as indicated by the magnitude of the Adjusted R Square while the rest79.5%influenced by other factors that are not included in the research model.